2008
DOI: 10.1111/j.1475-097x.2007.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Body fat related to daily physical activity and insulin concentrations in non‐diabetic children

Abstract: 1 SummaryThis study explored the associations between body fat versus daily physical activity and insulin concentrations in non-diabetic young children in a Cross-sectional study of 172 children (93 boys and 79 girls) aged 8 to 11 years. Blood samples were analysed for serum insulin and daily physical activity was measured by accelerometers. Time spent performing vigorous activity was estimated from accelerometer data by using established cut off points. Dual-energy x-ray absorptiometry (DXA) was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We found that being normal weight was associated with a higher % daily MVPA compared with being overweight/obese. Our result is in line with the findings for BMI and % body fat in other studies in which children's physical activity is assessed by accelerometers (Trost et al, 2001; Adkins et al, 2004; Dencker et al, 2008). The result could imply that being overweight/obese might be a barrier for engaging in physical activity when entering adolescence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that being normal weight was associated with a higher % daily MVPA compared with being overweight/obese. Our result is in line with the findings for BMI and % body fat in other studies in which children's physical activity is assessed by accelerometers (Trost et al, 2001; Adkins et al, 2004; Dencker et al, 2008). The result could imply that being overweight/obese might be a barrier for engaging in physical activity when entering adolescence.…”
Section: Discussionsupporting
confidence: 92%
“…There is no conclusive evidence for an association between body composition measures and children's physical activity in reviews (Sallis et al, 2000;van der Horst et al, 2007), but some studies with acceler-ometer-assessed physical activity have shown that a higher body mass index (BMI) and percent body fat is associated with less physical activity (Adkins et al, 2004;Dencker et al, 2008). In studies examining correlates using objective measures of physical activity, self-efficacy has been identified as a psychological correlate in children (Trost et al, 1999;Strauss et al, 2001;Dishman et al, 2009).…”
mentioning
confidence: 99%
“…However, our study period was short and involved physiological changes in body size consequently, further evaluation is required. These results were independent of factors that have been associated with high blood pressure, such as tobacco consumption (Shah et al, 2001), puberty (Shankar et al, 2005), physical activity (Dencker et al, 2008), and height (a variable reflecting an adjustment for ethnic variations) (Chiolero et al, 2007a). Still, our study has limitations, such as not having included other life history variables such as birth weight and diet, and in particular salt consumption (He et al, 2008), which has been shown to be involved in increased blood pressure in children and adolescents (Chiolero et al, 2007a).…”
Section: Discussionmentioning
confidence: 67%
“…Geographical locations varied across the studies with 7 conducted in the United States, 16-22 4 in Canada, 23-26 and 33 in Europe. 27-57 One study was conducted internationally 7 and the final study did not specify location. 58 Sample sizes varied considerably ranging from 36 to 6539 participants.…”
Section: Resultsmentioning
confidence: 99%